Fluid balance during physical work in the heat is not modified by the menstrual cycle when fluids are freely available - Freemas, J. A.; Goss, C. S.; Ables, R.; Baker, T. B.; Bruinvels, G.; Mündel, T.; Martin, B. J.; Carter, S. J.; Chapman, R. F.; Schlader, Z. J. (Journal of Applied Physiology, 2023)
We tested the hypothesis that women may be more at risk of becoming dehydrated during physical work in the heat in the early follicular phase (EF), compared with the late follicular (LF) and mid-luteal (ML) phases of the menstrual cycle when allowed free access to drink. Twelve healthy, eumenorrheic, unacclimated women (26 ± 5 yr) completed three trials (EF, LF, and ML phases) involving 4 h of exposure to 33.8 ± 0.8 °C, 54 ± 1% relative humidity. Each hour, participants walked on a treadmill for 30 min at a rate of metabolic heat production of 338 ± 9 W. Participants drank a cool, flavor-preferred non-caloric sport drink ad libitum. Nude body weight was measured pre- and post-exposure, and percent changes in body weight loss were interpreted as an index of changes in total body water. Total fluid intake and urine output were measured and sweat rate was estimated from changes in body mass corrected for fluid intake and urine output. Fluid intake was not different between phases (EF: 1,609 ± 919 mL; LF: 1,902 ± 799 mL; ML: 1,913 ± 671; P = 0.202). Total urine output (P = 0.543) nor sweat rate (P = 0.907) differed between phases. Percent changes in body mass were not different between phases (EF: -0.5 ± 0.9%; LF: -0.3 ± 0.9%; ML: -0.3 ± 0.7%; P = 0.417). This study demonstrates that the normal hormonal fluctuations that occur throughout the menstrual cycle do not alter fluid balance during physical work in the heat.